Wind and Wind Talk in the Prophet's Miracle - Analytical Study - Jamal Jabara Sultan,; Ghazi Nayef Hamid, (Islamic Sciences Journal, 2024)
ABSTRACT The sum of what I studied from the hadiths are three, and these hadiths were mentioned in the Two Sahihs, and it is proven that the honorable prophetic Sunnah is the second source of Islamic legislation, and it is a revelation from Allah, in which guidance, guidance, and happiness for human beings if they adhere to it, so the prophetic miracle is definitely proven, This is evidenced by the models that permeated this research, as the wind and the wind were associated with the prophetic miracle, as it is a soldier of God's soldiers, as Allah used it in many situations to prove the prophecy of the Prophet Muhammad (peace be upon him) exists in every era calling people to the religion of God and showing them evidence of its sincerity in a hadith that matches the new science with its discoveries, and that our saying of the prophetic miracle does not mean that we deal with it as a method, but rather we must know that it is an argument and evidence for prophecy.